Media Literacy and Information Security in Education - Terepyshchyi, Serhii; Kostenko, Anastasiia (Studia Warmińskie, 2021)
The article offers a research framework for analyzing the media literacy of such a special group of adults as educators. After all, people who have to stand guard over critical thinking and teach it to future generations are by no means safe from falling victim to a media attack or manipulation. The article proves that media literacy of an individual is no less important than previous forms of literacy. In the environment of modern communication media networks it is not enough to have only the simplest functional literacy, it is necessary to develop a deeper understanding of the nature and power of global interactivity. Although media literacy can generate several definitions, they are all designed to expand what is meant by literacy in general. The need for the introduction of an effective system of media literacy education for adults has been identified, which will significantly improve the level of information security in society.